D4.1 Report of the 1stsummer school - Brcic, Ramon; Eineder, Michael; Schreier, Gunter; Lysandrou, Vasiliki; Agapiou, Athos; Hadjimitsis, Diofantos G. (My University, 2016)
The specific deliverable summarizes the material related to the first summer school of the project entitled ‘Interferometry / Radar’. The deliverable includes actions completed prior the accomplishment of the summer school, such as the agenda prepared, as well as material deriving from the summer school per se, such as the presentations, the list of participants, picture with the participants and stakeholders etc.
Keywords: Interferometry; Radar